Analysis of teacher performance to build student interest and motivation towards mathematics achievement - Hardi Tambunan; Bornok Sinaga; Wahyu Widada (Institute of Advanced Engineering and Science, 2021)
The purpose of this study was to determine the impact and categories of teacher performance in building student interest and motivation on mathematics achievement. The population in this study was students in the eighth grade of junior high schools from six public and two private schools, and a sample of 277 students was taken by cluster sampling. Data collection instruments used a questionnaire, and data analysis was done by using by descriptive and path analysis. The results of data analysis showed that partially, teacher performance significantly affected student interest and motivation excel at mathematics. Simultaneously, teacher performance is very significant in influencing student interest and motivation to be excellent in mathematics. Partially, teacher performance builds interest and student motivation for mathematics achievement is low category. Simultaneously, teacher performance builds student interest and motivation to excel at mathematics is low category. Both of these can be caused by the ability of teachers to build motivation and interest is not good, so students are also less interested and motivated to learn mathematics.